Practice and analysis of calculation and collection of land tax from economic entities in Uzbekistan - Nasimdjanov Yunusjon Zokhidovich (Peerian Journals Publishing, 2023)
In this article, the practice and analysis of the calculation and collection of land tax from economic entities in Uzbekistan is presented. The importance of land resources in the national economy, strategic directions of the use of financial and credit mechanisms in their effective use are proposed. Also, the basics of land tax administration of legal entities were revealed and a proposal for their improvement was developed
Keywords: resource tax; subsoil tax; budget